“Peace for Our Time”: Reading Jonah in Dialogue with Abravanel in the Book of the Twelve - Lena-Sofia Tiemeyer (Journal of Hebrew Scriptures, 2017)
Many scholars struggle to understand the reasons behind Jonah's reluctance to go to Nineveh. Using Abravanel's interpretation as its starting point, namely that Jonah sought to ensure Israel's survival by refusing to prophesy to Nineveh, this article explores the notion of foreknowledge, shared by the authors and readers of Jonah. In particular, it asks how our knowledge of Nineveh's fall, inferred from both Nahum and history, influences our understanding of the message of Jonah.